Penerapan Model Pembelajaran Blended Learning Dalam Meningkatkan Hasil Belajar Siswa Kelas VII Pada Mata Pelajaran IPS Terpadu di SMPK Nirmala Jopu - Yovita Gaa; Marsel Nande (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2024)
The background of this research is because teachers who always apply conventional learning models during learning so that it has an impact on student learning outcomes. The purpose of this study was to determine (1) The application of the blended learning model in class VII at SMPK Nirmala Jopu; (2) The learning outcomes of class VII students at SMPK Nirmala Jopu in social studies subjects after applying the blended learning model. The research method used is classroom action research (PTK). Data collection techniques are carried out through observation, tests, and documentation. The results of the study showed that the observation of teacher activities in the application of the blended learning model in cycle I was 75 percent including the